Pengaruh Kualitas Air terhadap Kualitas Tanah pada Tata Saluran Irigasi Pasang Surut di Kab. Barito Kuala, Kalimantan Selatan - Tania Edna Bhakty (KEAIRAN, 2005)
The food production in South Kalimantan Province is mostly gained from tidal irrigation along the downstream of Barito river. Tabunganen unit an area of 5600 ha, is one of the area under Tabunganen subdistrict. Previously the rice production in Tabunganen unit was considered sufficient, with the production rate of 2,5-3,0 ton/ha. Currently some areas near the tidal ponds have very low productivity, around 1-1,5 ton/ha. Some farmers presume that the decline in productivity is caused by soil acidity. This research is aimed to investigate the influence of water quality on soil quality in Tabunganen unit. Some measurements are taken in secondary and tertiary channels (upstream, middle, downstream), the value of Fe (mg/l), DHL (mmhos) and pH. The flow and water quality measurements are taken every 3 hours within 26 hours. Water level is measured for 15 days. The result of this research shows that pH values in both secondary and tertiary (upstream, middle, downstream) are pH>6. During rise and fall tide, the pH values of the right and left ponds are still same. This condition indicated the disfunction of the ponds retaining soil acidity, especially some areas near the tidal ponds. Therefore, the field has high potency for pirit oxidation. In tertiary channel, the DHL values is DHL>3290 mmhos, pH value is 6<pH<7 and Fe value is 0,01-1 mg/l.Keywords:Water quality, tidal irrigation, Barito river Permalink: http://ejournal.undip.ac.id/index.php/keairan/article/view/2716[How to cite: Bhakty, T.E. (2005). Pengaruh Kualitas Air terhadap Kualitas Tanah pada Tata Saluran Irigasi Pasang Surut di Kab. Barito Kuala, Kalimantan Selatan, Jurnal Keairan, 12 (2): 1-14]